Docosahexaenoic Acid Included in Layer Feed as an Unextracted Aurantiochytrium limacinum Biomass Is Efficiently Transferred to Eggs When Provided in Mash or Pellet Form. (2nd August 2019) - Keegan, J D; Currie, D; Knox, A; Moran, C A
SUMMARY: Pelleting is commonly used in the production of poultry feed as it can reduce waste, kill pathogenic bacteria, and improve productivity. However, high temperatures used during production can negatively impact some feed ingredients. Omega-3 long-chain polyunsaturated fatty acid (n-3 LC-PUFA)-rich ingredients are often added to poultry feed to increase the n-3 LC-PUFA concentration of meat and eggs, adding value due to the health benefits associated with n-3 LC-PUFA consumption. Fish oils have traditionally been used for this purpose, but the n-3 LC-PUFA they contain are susceptible to oxidation, which can result in rancidity in enriched poultry products. Alternatively, protists that are primary producers of n-3 LC-PUFA are used. When provided in an unextracted form, these organisms could potentially protect the n-3 LC-PUFA they contain from oxidation. Aurantiochytrium limacinum is a marine protist, rich in docosahexaenoic acid (DHA), an n-3 LC-PUFA associated with various health benefits. We supplemented layer feed with A. limacinum and investigated the effect of pelleting on the recovery of DHA from feed and the efficiency of DHA transfer from feed to eggs. Pelleting did not decrease the concentration of DHA in feed. Also, no differences were observed between the groups fed mash or pelleted feeds in terms of the level of DHA enrichment of eggs. These results indicate that DHA, in the form of an A. limacinum biomass, is resistant to pelleting conditions and can be used as an ingredient in pelleted poultry diets to increase the DHA concentration of poultry products.